4. PERAN PEMERINTAH THAILAND DALAH MENGATASI PENCARI SUAKA ROHINGYA DI THAILAND - Augita, Sella; Windiani, Reni; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
This research aims to determine the cause of Thai Government's role on handling theissues of Rohingya’s asylum seekers, victims of ethnic conflict in Thailand. These problemsarise as a result of the conflict between ethnic Rakhine Buddhists and Rohingya Moslemsin Myanmar 2012, until eventually the Rohingya moslems fled from Myanmar seekingasylum to neighboring countries. English school of thought, concept of compliance andResponsibility to Protect or R2P, is used to explain the basis and forms of Thailandcompliance on the international organizations of the United Nations (UN), as well asThailand's responsibility to protect the Rohingya refugees and asylum seekers. Theresearch method is explanative which used to analyze and explain the various problems ofRohingya asylum seekers such as the existence of smuggling and trafficking of Rohingyaasylum seekers. Results from this research is the Thai government act in accordance withthe provisions of the United Nations and international law on handling Rohingya’s asylumseekers, as a form of allegiance to United Nations and also has the responsibility toprovide human right protection for Rohingya refugees. From these findings, thesuggestions that emerged was the Government of Thailand should ratify the 1951Convention and 1967 Protocol about the international refugee protection, in order forasylum seekers to gain firm and fair access to the procedure for sanctuary.